Strategi Marketing Communication melalui Event Energizing the Acceleration 67th PT. Pertamina Persero dalam Meningkatkan Brand Image IHC Klinik Pertamina - Fharhan Fadhlurrahman; Nita Noviati; Eka Harrdi Yudharsa (Comit: Communication, Information and Technology Journal, 2025)
This study analyzes the marketing communication strategy implemented in the "Energizing the Acceleration 67th" event by PT Pertamina (Persero) and its impact on the brand image of IHC Klinik Pertamina. Employing a descriptive qualitative approach, data were collected through semi-structured interviews with the marketing team, representatives of IHC Klinik Pertamina, and event organizers, supported by relevant documentation. The findings indicate that the communication strategy adhered to the eight stages of Integrated Marketing Communication (IMC) as proposed by Kotler and Keller, ranging from audience identification to communication evaluation. The continuous implementation of IMC, reinforced by emotional appeal, visual storytelling, and active audience participation, significantly enhanced the brand image of IHC Klinik Pertamina. Managerial implications include strengthening audience monitoring systems, mapping communication objectives, conducting media audits, and establishing a cross-divisional communication team to improve the effectiveness of future communication strategies.